Implementasi Algoritme Blake2s pada JSON Web Token (JWT) sebagai Algoritme Hashing untuk Mekanisme Autentikasi Layanan REST-API - Bagus Satria Wiguna; Ari Kusyanti; Widhi Yahya (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
REST is a web-based client-server communication architecture. REST server provides data in the form of URL to be accessed by client in JSON form. The disadvantage of current REST architecture is the lack of authentication mechanism which allows anyone to access, change, or delete data. To solve the authentication problem from REST architecture, is required an authentication system. JWT is a token that is proposed to authenticate and ensure message integrity. Using JWT on the REST architecture can provide authentication and security. In JWT Implementation there are various hash algorithms used, one of them is HMAC-SHA256 algorithm which is SHA256 algorithm using message authentication code (MAC). In 2011, the vulnerability of SHA256 is found which is preimage attack and pseudo collision attacks. BLAKE2S algorithm is an algorithm created in 2012 succeding BLAKE algorithm. BLAKE2S algorithm offers better security since it is built with HAIFA iteration and ChaCha stream cipher. This research implemented BLAKE2S algorithm on JWT for REST API service authentication mechanism as alternative HMAC-SHA256 algorithm. Test-vector is performed to ensure the test-vector given in RFC document. The Authentication process of BLAKE2S is 88.583 ms.